Thiazolinone acrylic acid silane ester self-polishing antifouling resin as well as preparation method and application thereof

The self-polishing anti-fouling resin of thiazolinone silane acrylate self-polishing anti-fouling resin in seawater and combined with silicon-based side chains, the problem of high toxicity of traditional coatings and poor self-polishing effect in static environments has been solved, and many Standard anti-fouling and environmentally friendly marine anti-fouling coatings.

CN119192458APending Publication Date: 2024-12-27HARBIN ENG UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411481446.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional marine antifouling coatings have high toxicity and damage to the marine environment. The existing environmentally friendly coatings have poor self-polishing effect in static environments, making it difficult to effectively resist the adhesion of multi-scale polluted organisms.

Method used

Using thiazolinone silane acrylate self-polishing antifouling resin, 5-chloro-2-benzothiazolinone is used to interpret the release of 5-chloro-2-benzothiazolinone in seawater, combining triisopropylsilylmethacrylate and phenyldimethylsil Basic methacrylate enhances the hydrophobicity and self-polishing properties of the resin, achieving rapid surface renewal and multi-scale anti-fouling effect.

Benefits of technology

It achieves rapid self-renewal in seawater and good self-polishing and anti-fouling effects under static environments, has the ability to resist multi-scale polluting organisms, and is environmentally friendly, reducing the harm to the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192458A_ABST
    Figure CN119192458A_ABST
Patent Text Reader

Abstract

The invention discloses a thiazolinone acrylic acid silane ester self-polishing antifouling resin and a preparation method and application of the thiazolinone acrylic acid silane ester self-polishing antifouling resin. The preparation method of the thiazolinone acrylic acid silane ester self-polishing antifouling resin mainly comprises the following steps: in a nitrogen environment, adding an initiator, the preparation method comprises the following steps: carrying out random free radical polymerization reaction on thiazolinone methacrylate, methyl methacrylate, ethyl acrylate, triisopropyl silicon-based methacrylate and phenyl dimethyl silicon-based methacrylate by taking azodiisobutyronitrile and benzoyl peroxide as initiators to synthesize the photoinitiator. Wherein the thiazolinone methacrylate monomer is prepared by grafting double bonds on 5-chloro-2-benzothiazolinone and methacryloyl chloride through a substitution reaction, then grafting hydroxyl on the 5-chloro-2-benzothiazolinone and mercaptoethanol through a mercapto-alkene click reaction and finally carrying out a substitution reaction on the 5-chloro-2-benzothiazolinone and methacryloyl chloride. According to the invention, the coating still has good surface self-renewal capability even in a static environment so as to inhibit the adhesion of large fouling organisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of marine antifouling coatings, and in particular to a thiazolinone-based silane acrylate self-polishing antifouling resin and a preparation method and application thereof. Background Art

[0002] my country has made great progress in shipbuilding and marine transportation. Compared with airplanes and other modes of transportation, marine transportation is a more cost-effective and environmentally friendly mode of transportation. However, the colonization of marine microorganisms and plants and animals on the surface of ships will change the roughness of the surface of ships, increase the navigation resistance and weight of ships, reduce the speed and increase fuel consumption and greenhouse gas emissions, which will have an adverse impact on my country's economic development and ecological environment. The application of antifouling coatings refers to coating the antifouling coating on the surface of the structure, using the characteristics of the coating itself or the active factors that seep out of the coating to kill or inhibit the growth and adhesion of fouling organisms. Among them, the self-polishing antifouling coating has the advantage of long antifouling time because the surface can be continuously self-renewed under the scouring of seawater, and is the main marine antifouling material currently used at home and abroad. However, although the traditional organotin self-polishing coating has a good antifouling effect, it is highly toxic and causes great damage to the marine ecological environment. Nowadays, Wuxi self-polishing antifouling coatings, such as zinc acrylate, copper acrylate and other low-toxic self-polishing antifouling coatings are widely used. However, metal ions such as copper and zinc still cause certain damage to the marine environment. Therefore, it is necessary to develop an environmentally friendly and excellent antifouling self-polishing antifouling resin.

[0003] Chinese patent CN115197360A discloses a method for preparing a fluorinated eugenol ester-based methacrylate self-polishing antifouling resin, which introduces bio-based eugenol into an acrylate self-polishing antifouling resin system. Under the weak alkaline environment of seawater, environmentally friendly eugenol with antibacterial properties is hydrolyzed to obtain an acrylate self-polishing resin that is friendly to the marine ecology.

[0004] Chinese patent CN117659259A discloses a method for preparing a vanillin ester-based acrylate self-polishing antifouling resin. The side chain phenolic ester group of vanillin methacrylate in the vanillin ester-based acrylate self-polishing antifouling resin can be hydrolyzed in seawater to achieve self-polishing, while releasing the antifouling active substance vanillin from the surface of the material. It is an environmentally friendly self-polishing antifouling resin that has resistance to multi-scale fouling organisms.

[0005] The present invention starts from a different inventive conception and introduces 5-chloro-2-benzothiazolinone into a disilyl acrylate self-polishing resin for the first time. Although the selection of some monomers is similar, the addition of phenyldimethylsilyl methacrylate and thiazolinone methacrylate enhances the surface self-renewal ability and static antifouling ability of traditional acrylic silane esters, which has not been studied in previous technologies. The inventors still need to make creative efforts to optimize and improve many aspects such as the synthesis process, the ratio of monomers, the selection of solvents, etc., in order to prepare an environmentally friendly self-polishing antifouling resin different from the prior art. Summary of the invention

[0006] Therefore, the purpose of the present invention is to propose a thiazolinone-based silane acrylate self-polishing antifouling resin and a preparation method and application thereof. The thiazolinone-based silane acrylate self-polishing antifouling resin can self-renew its surface quickly in seawater and has a good self-polishing antifouling effect even in a static environment. It is an environmentally friendly self-polishing antifouling resin that is resistant to multi-scale marine fouling organisms.

[0007] The technical solutions adopted are:

[0008] The present invention discloses a thiazolinone-based silane acrylate self-polishing antifouling resin, and its structural formula is as follows:

[0009]

[0010] Among them, a, b, c, d, and e are the numbers of repeating units in random copolymerization. The monomer repeated in a is methyl methacrylate; the monomer repeated in b is ethyl acrylate; the monomer repeated in c is triisopropylsilyl methacrylate; the monomer repeated in d is phenyldimethylsilyl methacrylate; the monomer repeated in e is thiazolinone methacrylate; and co represents random copolymerization of monomers.

[0011] A method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin of the present invention comprises the following steps, measured in parts by weight:

[0012] (1) 30-55 parts of methyl methacrylate, 10-25 parts of ethyl acrylate, 1-20 parts of thiazolinone methacrylate, 10-25 parts of triisopropylsilyl methacrylate, 5-15 parts of phenyldimethylsilyl methacrylate and 0.5-2 parts of azobisisobutyronitrile are mixed and dissolved in a mixed solution of not more than 30 parts of N,N-dimethylformamide and propylene glycol methyl ether;

[0013] (2) Add 50 parts of a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether into a four-necked flask and heat it to 80-90° C., slowly dropwise add the mixed solution of step (1) in a protective atmosphere, continue to dropwise add, and after the dropwise addition is completed, slowly add a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether containing 0.1-1 parts of benzoyl peroxide for secondary initiation, continue to dropwise add, and then maintain the same temperature and continue to stir to ensure sufficient reaction, and finally obtain a thiazolinone-based silane acrylate self-polishing antifouling resin.

[0014] Furthermore, in step (1), the thiazolinone methacrylate is obtained by the following preparation method, which comprises the following steps in parts by weight:

[0015] 1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.5-1.5 parts of triethylamine, an acid-binding agent, in 10-30 parts of tetrahydrofuran; slowly dropping 0.5-1.5 parts of methacryloyl chloride into the above solution at a low temperature of 0-5°C, stirring continuously during the whole process; stirring at room temperature after the dropwise addition is completed to fully react; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine to obtain thiazolinone-based methacrylamide;

[0016] 2) dissolving 1 part of thiazolinone methacrylamide, 0.8-1.5 parts of β-mercaptoethanol and 0.001-0.005 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, stirring for 2-5 hours under protective atmosphere and ultraviolet light, precipitating the product in distilled water for 2-5 times, and vacuum drying at 60° C. for 24-36 hours to obtain hydroxy-modified thiazolinone amide;

[0017] 3) dissolving 1 part of hydroxy-modified thiazolinone amide and 1.2-1.5 parts of acid-binding agent triethylamine in 4-10 parts of tetrahydrofuran; slowly dropping 1.05-1.1 parts of methacryloyl chloride into the above solution at a low temperature of 0-5°C, stirring continuously during the process, stirring at room temperature after the dropwise addition is completed to fully react; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine to obtain a thiazolinone methacrylate monomer.

[0018] Furthermore, in step (1), the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether is 2:1.

[0019] Furthermore, in step (2), after the mixed solution of step (1) is added dropwise, it is stirred at room temperature for sufficient reaction for 12-36 hours.

[0020] Furthermore, in step (2), the protective atmosphere is one or more of nitrogen, argon, and helium.

[0021] Furthermore, in step (2), the mixed solution of step (1) is slowly added dropwise in a protective atmosphere at a dropping speed of 30-50 parts / hour.

[0022] Further, in step (2), the mixed solution of N,N-dimethylformamide and propylene glycol methyl ether containing 0.1-1 parts of benzoyl peroxide is continuously added dropwise for 30 minutes, and then the same temperature is maintained and stirred for 3 hours to ensure sufficient reaction. The mixed solution of N,N-dimethylformamide and propylene glycol methyl ether containing 0.1-1 parts of benzoyl peroxide is prepared by adding 0.1-1 parts of benzoyl peroxide to the mixed solution of N,N-dimethylformamide and propylene glycol methyl ether.

[0023] The thiazolinone-based silane acrylic acid ester self-polishing antifouling resin of the present invention is used in the preparation of marine antifouling coatings.

[0024] Furthermore, the ester groups contained in the thiazolinone methacrylate, triisopropylsilyl methacrylate and phenyl dimethylsilyl methacrylate in the thiazolinone silane acrylate self-polishing antifouling resin can be hydrolyzed in the ocean to quickly renew the coating surface. The hydrolysis reaction formula of the thiazolinone acrylate self-polishing antifouling resin is as follows:

[0025]

[0026] In the above technical solution,

[0027] (1) Thiazolinone methacrylate is a functional monomer with broad-spectrum antifouling ability. After contact with weakly alkaline seawater, both the ester bond and the amide bond can be hydrolyzed, so that 5-chloro-2-benzothiazolinone can be released from the coating surface, which can kill fouling organisms and thus achieve the antifouling purpose.

[0028] (2) The addition of triisopropylsilyl methacrylate not only ensures the hydrophobicity of the resin, but also enables it to have dynamic self-polishing properties.

[0029] (3) The hydrolysis performance of the resin side chain is adjusted by phenyl dimethylsilyl methacrylate, thereby enhancing the surface self-renewal performance of the resin in a static environment.

[0030] (4) The glass transition temperature, hardness and flexibility of the resin are adjusted by methyl methacrylate and ethyl acrylate.

[0031] (5) Using a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether as the solvent has good compatibility with the resin and makes the coating easy to solidify. Controlling the resin solid content at about 40% can ensure that the resin viscosity is moderate, can be stored for a long time, and is convenient for coating application.

[0032] In order to inhibit the adhesion of marine biofouling on the surface of marine infrastructure and ships, the present invention creatively introduces thiazolinone methacrylate and phenyldimethylsilyl methacrylate functional monomers into the acrylic silane self-polishing system, and successfully prepares a thiazolinone acrylic silane antifouling resin by random free radical copolymerization with other acrylic ester monomers. The ester group and amide bond of the side chain can be hydrolyzed in the seawater environment to release 5-chloro-2-benzothiazolinone to resist the attachment of small fouling organisms such as bacteria and algae. In addition, the hydrolysis of the two silicon-based side chains increases the carboxyl groups on the coating surface, resulting in enhanced hydrophilicity, and ultimately causes the main chain to fall off and renew the surface, which can resist the attachment of large fouling organisms. Ultimately, an environmentally friendly self-polishing antifouling resin that can resist multi-scale fouling organisms can be constructed.

[0033] In summary, compared with the prior art, the beneficial effects of the present invention are:

[0034] 1. The present invention introduces the environmentally friendly and easy-to-prepare thiazolinone-based methacrylate antifouling monomer into the field of acrylic silane self-polishing antifouling coatings for the first time, and has certain application prospects.

[0035] 2. Utilize the hydrolysis of ester and amide bonds of thiazolinone methacrylate in a weakly alkaline environment to release 5-chloro-2-benzothiazolinone to break the bonds of proteins in bacteria and algae, thereby inhibiting or even killing bacteria and algae.

[0036] 3. By introducing a variety of hydrolyzable monomers, the resin can be hydrolyzed faster in seawater and has a good surface self-renewal effect in a static environment.

[0037] 4. The self-polishing speed and service life of the resin can be regulated by controlling the ratio of triisopropylsilyl methacrylate, phenyldimethylsilyl methacrylate and thiazolinone methacrylate.

[0038] 5. Marine antifouling coatings achieve surface self-renewal through the hydrolysis of the side chain ester group and amide bond of thiazolinone-based silyl acrylate in seawater, while releasing the antifouling active substance 5-chloro-2-benzothiazolinone from the surface of the material, giving the coating a dual antifouling capability of "defense-offense".

[0039] In summary, the thiazolinone-based silyl acrylate self-polishing antifouling resin of the present invention is a type of coating that enables the coating surface to self-renew through side chain hydrolysis. In a seawater environment, the ester group and amide bond on the side chain of the resin will be broken by hydrolysis to release the antifouling active substance 5-chloro-2-benzothiazolinone, and the main chain will gradually become brittle as the hydrophilic carboxyl group increases, thereby exposing a new antifouling surface under seawater scouring. Compared with traditional zinc / copper acrylate and silyl acrylate antifouling coatings, the present invention introduces eco-friendly 5-chloro-2-benzothiazolinone into the self-polishing antifouling resin. 5-chloro-2-benzothiazolinone has excellent antibacterial and algaecidal capabilities to inhibit the adhesion of primary fouling organisms. At the same time, the dual silane ester monomers of triisopropylsilyl methacrylate and phenyldimethylsilyl methacrylate are introduced to accelerate the renewal rate of the coating surface, so that the coating still has good surface self-renewal ability even in a static environment to inhibit the adhesion of large fouling organisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The contact angle test results of the thiazolinone-based silane acrylate self-polishing antifouling coating before and after hydrolysis in artificial seawater and deionized water for 120 hours;

[0041] Figure 2 This is the hydrolysis weight loss curve of the thiazolinone-based silane acrylate self-polishing antifouling coating in artificial seawater for 31 days;

[0042] Figure 3 This is the fluorescence confocal microscopy image of the experimental results of the thiazolinone-based silane acrylate self-polishing antifouling coating against Amphiprion and Nitzschia closterii.

[0043] Figure 4 This is a graph showing the results of the anti-Dinocampal algae test of the thiazolinone-based silane acrylate self-polishing antifouling coating;

[0044] Figure 5 This is a graph showing the results of the anti-Nitzschia closterium experiment of the thiazolinone-based silane acrylate self-polishing antifouling coating;

[0045] Figure 6 This is a digital photo of the antibacterial test results of the thiazolinone-based silane acrylate self-polishing antifouling coating;

[0046] Figure 7 It is the result of the anti-Escherichia coli test of thiazolinone-based silane acrylate self-polishing antifouling coating;

[0047] Figure 8 The results of the anti-Staphylococcus aureus test of thiazolinone-based silane acrylate self-polishing antifouling coating;

[0048] Fig. 9 These are the test results of the thiazolinone-based silane acrylate self-polishing antifouling coating against Pseudoalteromonas Xiamen. DETAILED DESCRIPTION

[0049] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.

[0050] Unless otherwise specified, the parts in the following examples are parts by weight.

[0051] Example 1

[0052] A thiazolinone-based silane acrylate self-polishing antifouling resin of this embodiment is prepared by the following steps:

[0053] 1. Synthesis of Thiazolinone Methacrylate

[0054] (1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.9 parts of triethylamine, an acid binder, in 10 parts of tetrahydrofuran; slowly dropping 0.6 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0° C., stirring continuously, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine, thereby obtaining thiazolinone-based methacrylamide;

[0055] (2) Dissolve 1 part of thiazolinone methacrylic acid amide, 0.85 parts of 2-mercaptoethanol and 0.03 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, and stir for 3 hours under ultraviolet light and protective gas. The obtained product is precipitated in deionized water for 3 times and vacuum dried at 60° C. for 24 hours to obtain hydroxyl-modified thiazolinone amide;

[0056] (3) Dissolving 1 part of hydroxy-modified thiazolinone amide and 0.5 parts of acid-binding agent triethylamine in 10 parts of tetrahydrofuran; slowly dropping 0.4 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0°C, stirring continuously during the process, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove the tetrahydrofuran and triethylamine, thereby obtaining a thiazolinone methacrylate monomer.

[0057] 2. Synthesis of Thiazolinone-based Silane Methacrylate Self-polishing Antifouling Resin

[0058] (1) 38.8 parts of methyl methacrylate, 15.6 parts of ethyl acrylate, 15.6 parts of triisopropylsilyl methacrylate, 10 parts of phenyldimethylsilyl methacrylate, 20 parts of thiazolinone methacrylate and 1.2 parts of azobisisobutyronitrile were dissolved in a mixed solution of 50 parts of N,N-dimethylformamide and propylene glycol methyl ether (the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether was 2:1).

[0059] (2) Add 40 parts of N,N-dimethylformamide to a 1L four-necked flask and heat to 80°C. Add the above mixed solution dropwise in a nitrogen atmosphere. Stir continuously during the addition process at a stirring speed of 150rpm. The addition is completed in 3 hours. After the addition is completed, add a mixed solution (10 parts) of N,N-dimethylformamide and propylene glycol methyl ether dissolved with 0.32 parts of benzoyl peroxide dropwise for 30 minutes for secondary initiation. Then maintain 80°C and continue stirring for 3 hours to ensure sufficient reaction. Finally, a thiazolinone-based methacrylate silane self-polishing antifouling resin is obtained, which can be directly used to prepare marine antifouling coatings. The resin is named MBECT-20.

[0060] Coating performance characterization

[0061] (1) Laboratory contact angle test: The static contact angle of the thiazolinone-based methacrylate silane self-polishing antifouling coating before and after hydrolysis in artificial seawater and deionized water was measured using OCA-20. Figure 1 The contact angle comparison diagram of the sample prepared in Example 1 before and after hydrolysis in artificial seawater and deionized water for 120 hours shows that the contact angle decreases after hydrolysis, decreasing from 84.7° to 52.0° and 60.6° respectively.

[0062] (2) Laboratory static self-polishing test: Weigh the mass of a glass sheet with a size of 2.5 cm×7.5 cm, evenly apply the sample of Example 1 on the glass sheet, weigh the mass after complete curing, soak it in artificial seawater for 31 days, take it out and dry it, weigh it, and calculate the weight loss rate of the coating, which is calculated by the following formula (a):

[0063]

[0064] Where M is the weight loss rate of the coating, M0 is the mass of the blank glass sheet, M1 is the total mass of the coating and the glass sheet after the sample is completely cured, and M2 is the total mass of the coating and the glass sheet after the sample is immersed for 31 days and completely dried.

[0065] The calculated weight loss rate is 27.65%.

[0066] (3) Laboratory static diatom inhibition experiment: The sample of Example 1 was evenly smeared on a glass slide with a size of 2.5 cm × 3.5 cm, and a blank glass slide was selected as a blank control. The sample and the blank glass slide were immersed in two model algae species (Dinocampus divaricata and Nitzschia closterium) and immersed in the algae solution for 7 days. After the samples were taken out, the unattached algae were washed away, and the algae attachment on the coating was photographed under a fluorescence confocal microscope ( Figure 3 ), 5 areas were randomly selected for each coating to be photographed, and the average number of diatoms on the blank slide and the sample of Example 1 was calculated by the following formula (b):

[0067]

[0068] Where K is the inhibition rate of diatom attachment, N B is the average number of diatoms on the surface of the blank slide, and N is the average number of diatoms on the surface of the sample.

[0069] Calculate the inhibition rate of the attachment of the double-browed algae ( Figure 4 ) and inhibiting the attachment rate of Nitzschia closterium ( Figure 5 ) are 98.92% and 99.78% respectively.

[0070] (4) Laboratory static antibacterial experiment: The sample coating size was made into 2.5 cm × 3.5 cm, and a glass slide was selected as the blank control. The sample and the blank were co-cultured with bacteria at 37°C (Escherichia coli, Staphylococcus aureus) and Pseudomonas Xiamenensis was cultured at 28°C for 12 h and 24 h. After dilution to equal concentration, the bacterial solution was spread on the solid culture medium by the plate spreading method (each sample was spread in parallel 3 times), and incubated at 37°C and 28°C for 12 h and 24 h. The plates were taken out and the number of bacteria adhering to the coating surface was determined by plate counting. Figure 6 This is a digital picture of the antibacterial test results of the thiazolinone-based methacrylate silane self-polishing antifouling coating. It can be seen that the number of colonies on the coating surface is significantly reduced compared to the blank. The colony counting method is used to calculate the number of colonies on the sample and the blank. Figure 7 , Figure 8 and Fig. 9 The antibacterial rates of the thiazolinone-based methacrylate silane self-polishing antifouling coating are 57.8%, 62.0% and 94.9% respectively.

[0071] The test was carried out according to the test method of Example 1, and the results were as follows: the static contact angle of the thiazolinone-based methacrylate silane self-polishing antifouling coating decreased from 84.7° to 52.0° and 60.6° respectively after being immersed in artificial seawater and deionized water for 120 hours; the hydrolysis weight loss rate was 27.65%; the inhibition rate of Ampelopsis thaliana was 98.92%, and the inhibition rate of Nitzschia closterium was 99.78%; the inhibition rate of Escherichia coli was 57.8%, the inhibition rate of Aureococcus aureus was 62.0%, and the inhibition rate of Pseudoalteromonas xiamenensis was 94.9%.

[0072] Example 2

[0073] A thiazolinone-based silane acrylate self-polishing antifouling resin of this embodiment is prepared by the following steps:

[0074] 1. Synthesis of Thiazolinone Methacrylate

[0075] (1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.9 parts of triethylamine, an acid binder, in 10 parts of tetrahydrofuran; slowly dropping 0.6 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0° C., stirring continuously, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine, thereby obtaining thiazolinone-based methacrylamide;

[0076] (2) Dissolve 1 part of thiazolinone methacrylic acid amide, 0.85 parts of 2-mercaptoethanol and 0.03 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, and stir for 3 hours under ultraviolet light and protective gas. The obtained product is precipitated three times in deionized water and vacuum dried at 60° C. for 24 hours to obtain hydroxyl-modified thiazolinone amide;

[0077] (3) Dissolving 1 part of hydroxy-modified thiazolinone amide and 0.5 parts of acid-binding agent triethylamine in 10 parts of tetrahydrofuran; slowly dropping 0.4 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0°C, stirring continuously during the process, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove the tetrahydrofuran and triethylamine, thereby obtaining a thiazolinone methacrylate monomer.

[0078] 2. Synthesis of Thiazolinone-based Silane Methacrylate Self-polishing Antifouling Resin

[0079] (1) 41.7 parts of methyl methacrylate, 16.7 parts of ethyl acrylate, 16.7 parts of triisopropylsilyl methacrylate, 10 parts of phenyldimethylsilyl methacrylate, 15 parts of thiazolinone methacrylate and 1.2 parts of azobisisobutyronitrile were dissolved in a mixed solution of 50 parts of N,N-dimethylformamide and propylene glycol methyl ether (the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether was 2:1).

[0080] (2) Add 40 parts of N,N-dimethylformamide to a 1L four-necked flask and heat to 80°C. Add the above mixed solution dropwise in a nitrogen atmosphere. Stir continuously during the addition process at a stirring speed of 150rpm. The addition is completed in 3 hours. After the addition is completed, add a mixed solution (10 parts) of N,N-dimethylformamide and propylene glycol methyl ether dissolved with 0.32 parts of benzoyl peroxide dropwise for 30 minutes for secondary initiation. Then, maintain 80°C and continue stirring for 3 hours to ensure sufficient reaction. Finally, a thiazolinone-based methacrylate silane self-polishing antifouling resin is obtained, which can be directly used to prepare marine antifouling coatings. The resin is named MBECT-15.

[0081] The test was carried out according to the test method of Example 1, and the results were as follows: the static contact angle of the thiazolinone-based methacrylate silane self-polishing antifouling coating decreased from 87.4° to 58.1° and 63.4° respectively after being immersed in artificial seawater and deionized water for 120 hours; the hydrolysis weight loss rate was 22.04%; the inhibition rate of Ampelopsis thaliana was 97.84%, and the inhibition rate of Nitzschia closterium was 99.29%; the inhibition rate of Escherichia coli was 51.3%, the inhibition rate of Aureococcus aureus was 51.0%, and the inhibition rate of Pseudoalteromonas xiamenensis was 83.0%.

[0082] Example 3

[0083] A thiazolinone-based silane acrylate self-polishing antifouling resin of this embodiment is prepared by the following steps:

[0084] 1. Synthesis of Thiazolinone Methacrylate

[0085] (1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.9 parts of triethylamine, an acid binder, in 10 parts of tetrahydrofuran; slowly dropping 0.6 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0° C., stirring continuously, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine, thereby obtaining thiazolinone-based methacrylamide;

[0086] (2) Dissolve 1 part of thiazolinone methacrylic acid amide, 0.85 parts of 2-mercaptoethanol and 0.03 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, and stir for 3 hours under ultraviolet light and protective gas. The obtained product is precipitated three times in deionized water and vacuum dried at 60° C. for 24 hours to obtain hydroxyl-modified thiazolinone amide;

[0087] (3) Dissolving 1 part of hydroxy-modified thiazolinone amide and 0.5 parts of acid-binding agent triethylamine in 10 parts of tetrahydrofuran; slowly dropping 0.4 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0°C, stirring continuously during the process, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove the tetrahydrofuran and triethylamine, thereby obtaining a thiazolinone methacrylate monomer.

[0088] 2. Synthesis of Thiazolinone-based Silane Methacrylate Self-polishing Antifouling Resin

[0089] (1) 44.4 parts of methyl methacrylate, 17.8 parts of ethyl acrylate, 17.8 parts of triisopropylsilyl methacrylate, 10 parts of phenyldimethylsilyl methacrylate, 10 parts of thiazolinone methacrylate and 1.2 parts of azobisisobutyronitrile were dissolved in a mixed solution of 50 parts of N,N-dimethylformamide and propylene glycol methyl ether (the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether was 2:1).

[0090] (2) Add 40 parts of N,N-dimethylformamide to a 1L four-necked flask and heat to 80°C. Add the above mixed solution dropwise in a nitrogen atmosphere. Stir continuously during the addition process at a stirring speed of 150rpm. The addition is completed in 3 hours. After the addition is completed, add a mixed solution (10 parts) of N,N-dimethylformamide and propylene glycol methyl ether dissolved with 0.32 parts of benzoyl peroxide dropwise for 30 minutes for secondary initiation. Then maintain 80°C and continue stirring for 3 hours to ensure sufficient reaction. Finally, a thiazolinone-based methacrylate silane self-polishing antifouling resin is obtained, which can be directly used to prepare marine antifouling coatings. The resin is named MBECT-10.

[0091] The test was carried out according to the test method of Example 1, and the results were as follows: the static contact angle of the thiazolinone-based methacrylate silane self-polishing antifouling coating decreased from 88.9° to 58.4° and 63.2° respectively after being immersed in artificial seawater and deionized water for 120 hours; the hydrolysis weight loss rate was 19.28%; the inhibition rate of Ampelopsis thaliana was 92.67%, and the inhibition rate of Nitzschia closterium was 99.17%; the inhibition rate of Escherichia coli was 38.5%, the inhibition rate of Aureus coccus was 40.8%, and the inhibition rate of Pseudoalteromonas xiamenensis was 78.2%.

[0092] Example 4

[0093] A thiazolinone-based silane acrylate self-polishing antifouling resin of this embodiment is prepared by the following steps:

[0094] 1. Synthesis of Thiazolinone Methacrylate

[0095] (1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.9 parts of triethylamine, an acid binder, in 10 parts of tetrahydrofuran; slowly dropping 0.6 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0° C., stirring continuously, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine, thereby obtaining thiazolinone-based methacrylamide;

[0096] (2) Dissolve 1 part of thiazolinone methacrylic acid amide, 0.85 parts of 2-mercaptoethanol and 0.03 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, and stir for 3 hours under ultraviolet light and protective gas. The obtained product is precipitated three times in deionized water and vacuum dried at 60° C. for 24 hours to obtain hydroxyl-modified thiazolinone amide;

[0097] (3) Dissolving 1 part of hydroxy-modified thiazolinone amide and 0.5 parts of acid-binding agent triethylamine in 10 parts of tetrahydrofuran; slowly dropping 0.4 parts of methacryloyl chloride dissolved in 10 parts of tetrahydrofuran into the above solution at 0°C, stirring continuously during the process, and stirring at room temperature for 24 hours after the dropwise addition is completed; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove the tetrahydrofuran and triethylamine, thereby obtaining a thiazolinone methacrylate monomer.

[0098] 2. Synthesis of Thiazolinone-based Silane Methacrylate Self-polishing Antifouling Resin

[0099] (1) 47.2 parts of methyl methacrylate, 18.9 parts of ethyl acrylate, 18.9 parts of triisopropylsilyl methacrylate, 10 parts of phenyldimethylsilyl methacrylate, 5 parts of thiazolinone methacrylate and 1.2 parts of azobisisobutyronitrile were dissolved in a mixed solution of 50 parts of N,N-dimethylformamide and propylene glycol methyl ether (the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether was 2:1).

[0100] (2) Add 40 parts of N,N-dimethylformamide to a 1L four-necked flask and heat to 80°C. Add the above mixed solution dropwise in a nitrogen atmosphere. Stir continuously during the addition process at a stirring speed of 150rpm. The addition is completed in 3 hours. After the addition is completed, add a mixed solution (10 parts) of N,N-dimethylformamide and propylene glycol methyl ether dissolved with 0.32 parts of benzoyl peroxide dropwise for 30 minutes for secondary initiation. Then maintain 80°C and continue stirring for 3 hours to ensure sufficient reaction. Finally, a thiazolinone-based methacrylate silane self-polishing antifouling resin is obtained, which can be directly used to prepare marine antifouling coatings. The resin is named MBECT-5.

[0101] The test was carried out according to the test method of Example 1, and the results were as follows: the static contact angle of the thiazolinone-based methacrylate silane self-polishing antifouling coating decreased from 88.4° to 58.5° and 64.0° respectively after being immersed in artificial seawater and deionized water for 120 hours; the hydrolysis weight loss rate was 12.34%; the inhibition rate of Ampelopsis thaliana was 81.49%, and the inhibition rate of Nitzschia closterium was 89.92%; the inhibition rate of Escherichia coli was 22.1%, the inhibition rate of Aureus coccus was 31.5%, and the inhibition rate of Pseudoalteromonas xiamenensis was 62.5%.

[0102] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A thiazolinone-based silane acrylate self-polishing antifouling resin, the structural formula of which is as follows: Among them, a, b, c, d, and e are the numbers of repeating units in random copolymerization. The monomer repeated in a is methyl methacrylate; the monomer repeated in b is ethyl acrylate; the monomer repeated in c is triisopropylsilyl methacrylate; the monomer repeated in d is phenyldimethylsilyl methacrylate; the monomer repeated in e is thiazolinone methacrylate; and co represents random copolymerization of monomers.

2. A method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 1, characterized in that: The method comprises the following steps, in parts by weight: (1) 30-55 parts of methyl methacrylate, 10-25 parts of ethyl acrylate, 1-20 parts of thiazolinone methacrylate, 10-25 parts of triisopropylsilyl methacrylate, 5-15 parts of phenyldimethylsilyl methacrylate and 0.5-2 parts of azobisisobutyronitrile are mixed and dissolved in a mixed solution of not more than 30 parts of N,N-dimethylformamide and propylene glycol methyl ether; (2) Add 50 parts of a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether into a four-necked flask and heat it to 80-90° C., slowly dropwise add the mixed solution of step (1) in a protective atmosphere, continue to dropwise add, and after the dropwise addition is completed, slowly add a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether containing 0.1-1 parts of benzoyl peroxide for secondary initiation, continue to dropwise add, and then maintain the same temperature and continue to stir to ensure sufficient reaction, and finally obtain a thiazolinone-based silane acrylate self-polishing antifouling resin.

3. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 2, characterized in that: In step (1), the thiazolinone methacrylate is obtained by the following preparation method, which comprises the following steps in parts by weight: 1) dissolving 1 part of 5-chloro-2-benzothiazolinone and 0.5-1.5 parts of triethylamine, an acid-binding agent, in 10-30 parts of tetrahydrofuran; slowly dropping 0.5-1.5 parts of methacryloyl chloride into the above solution at a low temperature of 0-5°C, stirring continuously during the whole process; stirring at room temperature after the dropwise addition is completed to fully react; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine to obtain thiazolinone-based methacrylamide; 2) dissolving 1 part of thiazolinone methacrylamide, 0.8-1.5 parts of β-mercaptoethanol and 0.001-0.005 parts of photoinitiator benzoin dimethyl ether in 50 parts of tetrahydrofuran, stirring for 2-5 hours under protective atmosphere and ultraviolet light, precipitating the product in distilled water for 2-5 times, and vacuum drying at 60° C. for 24-36 hours to obtain hydroxy-modified thiazolinone amide; 3) dissolving 1 part of hydroxy-modified thiazolinone amide and 1.2-1.5 parts of acid-binding agent triethylamine in 4-10 parts of tetrahydrofuran; slowly dropping 1.05-1.1 parts of methacryloyl chloride into the above solution at a low temperature of 0-5°C, stirring continuously during the process, stirring at room temperature after the dropwise addition is completed to fully react; filtering the reaction mixture to remove the ammonium salt precipitate, taking the filtrate, and vacuum drying to remove tetrahydrofuran and triethylamine to obtain a thiazolinone methacrylate monomer.

4. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 3, characterized in that: In step (1), the mass ratio of N,N-dimethylformamide to propylene glycol methyl ether is 2:

1.

5. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 2, characterized in that: In step (2), after the mixed solution of step (1) is added dropwise, it is stirred at room temperature for sufficient reaction for 12-36 hours.

6. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 2, characterized in that: In step (2), the protective atmosphere is one or more of nitrogen, argon and helium.

7. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 2, characterized in that: In step (2), the mixed solution of step (1) is slowly added dropwise in a protective atmosphere at a rate of 30-50 parts per hour.

8. The method for preparing the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 2, characterized in that: In step (2), a mixed solution of N,N-dimethylformamide and propylene glycol methyl ether containing 0.1-1 parts of benzoyl peroxide is continuously added dropwise for 30 minutes, and then stirred for 3 hours while maintaining the same temperature to ensure sufficient reaction.

9. Use of the thiazolinone-based silane acrylate self-polishing antifouling resin according to claim 1 in the preparation of marine antifouling coatings.

10. The use according to claim 9, characterized in that: The ester groups contained in the thiazolinone methacrylate, triisopropylsilyl methacrylate and phenyl dimethylsilyl methacrylate in the thiazolinone silane acrylate self-polishing antifouling resin can be hydrolyzed in the ocean to quickly renew the coating surface. The hydrolysis reaction formula of the thiazolinone acrylate self-polishing antifouling resin is as follows:

Citation Information

Cited By

  • Corrosion-resistant metal surface composite coating material and preparation method thereof

    CN119615316A

  • High-solid bio-based acrylate coating and preparation method thereof

    CN121249226A

  • Preparation method of paeonol fluorosilane methacrylate self-polishing antifouling resin and antifouling paint

    CN122587108A